2012
DOI: 10.3923/pjbs.2012.936.941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamins A, E and C on Liver Enzyme Activity in Rats Exposed to Organophosphate Pesticide Diazinon

Abstract: Diazinon, a commonly used organophosphorus pesticide, has been widely used throughout the world in agriculture and horticulture to control insects that feed on crops, ornamentals, lawns, fruits, vegetables and other food products. The toxicity of the DZN causes adverse effects on many organs. The purpose of this study was to examine the protective effect of vitamins A, E and C on liver enzymes alanine transaminase (ALT), Aspartate aminotransferase (AST) and Lactate Dehydrogenase (LDH) in rats exposed to diazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Also, Shokrzadeh et al (2012) revealed that Vit. E, A, and C have a protective effect against diazinon-induced hepatotoxicity in rats, as it increased the antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Shokrzadeh et al (2012) revealed that Vit. E, A, and C have a protective effect against diazinon-induced hepatotoxicity in rats, as it increased the antioxidant status.…”
Section: Discussionmentioning
confidence: 99%
“…Nanomaterials have recently attracted a lot of attention for their potential application as nanomedicines. Antioxidants such as vitamins, trace minerals, and medicines have all been widely used to combat oxidative stress (Shokrzadeh et al 2012;Lasram et al 2014) but with a lot of limitations. Scientific contributions to this research area reveal that some NPs have a free radical scavenging activity and hence have proved effective in oxidative stress conditions (Caputo et al 2014;Karakoti et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In some studies similar to ours, the effects of vitamins E, A, and C on rats with diazinon were investigated and the levels of AST and ALT decreased after these compounds were administered. According to these results, the vitamins protected against liver effects of diazinon and also may have radical cleansing and antioxidant properties [37]. In another study, the effect of vitamin E (600 mg) on sick and normal groups was investigated for 6 days.…”
Section: Resultsmentioning
confidence: 99%